The health impacts of women's low control in their living environment: A theory-based systematic review of observational studies in societies with profound gender discrimination. (May 2018) - Pennington, Andy; Orton, Lois; Nayak, Shilpa; Ring, Adele; Petticrew, Mark; Sowden, Amanda; White, Martin; Whitehead, Margaret
Abstract: We conducted a systematic review of observational evidence on the health impacts of women's low control/autonomy in the living environment in societies with profound gender discrimination and gender bias. Thirty observational studies of varying methodological quality were included. Overall, the evidence suggests that women's lower control or autonomy (for example lack of freedom of movement outside the home, lack of authority to access healthcare for sick children) was associated with poorer mental and physical health for women and higher morbidity and mortality for their children, after adjusting for their socioeconomic circumstances. Further studies are needed to disentangle and understand the pathways between low control and health outcomes in contexts of profound gender discrimination. This systematic review has highlighted the general low quality of the evidence base on this research question. It identifies the pressing need for high quality, longitudinal studies in the future. Highlights: Theory posits that restricted autonomy of women in societies with profound gender discrimination may lead to poorer health. Lower control over health determinants in their living environment may lead to poorer health outcomes for women and children. This theory-based systematic review examined the impact of women's low control in the living environment on health outcomes. The evidence suggests that women's low control in their living environment is associated with adverse health outcomes. There are adverse effects on the health of women and their children in societies with profound gender discrimination. Further high quality longitudinal studies are needed to disentangle and understand these pathways in greater depth.